Patient-and Family-Centered Care and Patient Safety: reflections upon emerging proximity - Andréia Cascaes Cruz; Mavilde da Luz Gonçalves Pedreira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To present reflections upon conceptual and pragmatic relationships between the Patient-and Family-Centered Care and patient safety. Method: A discussion about constructs related to the Patient-and Family-Centered Care and patient safety, which shows their interface with pragmatic issues of clinical nursing practice. Results: Considering patients and families as partners and agents promoting safe care is mandatory for the safety culture. Final considerations: Decreasing errors and adverse health care events can be accomplished by understanding manners to incorporate the principles of Patient-and Family-Centered Care into issues related to patient safety.